(untitled) (Historia, 2021)
Cherryl Walker’s insightful and authoritative monograph, in part a reworking of material published over the course of the last eight years, explores and assesses the work of South Africa’s land restitution programme since its formal inception in the early 1990s. A central project ties together a range of well-informed and superbly articulated critiques of restitution, that is, the "unstable authority" and meaning of land in national politics and local contexts.